Effectiveness of nursing case management versus usual care for blood pressure control in adults with hypertension: a systematic review - Maria de Fátima Mantovanil; Luciana Puchalski Kalinke; Ângela Taís Mattei da Silva; Juliana Perez Arthur; Cremilde Aparecida Trindade Radovanovic; Carina Bortolato-Major (Universidad de Antioquia, 2021)
Objective. To synthesize the best available evidence regarding the effectiveness of nursing case management in primary health care, compared to usual care, in improving blood pressure in adults over 18 years with hypertension. Methods. Systematic review that includes studies carried out with adult patients diagnosed with hypertension, with or without other concomitant chronic diseases, followed-up by a case manager nurse, who evaluated the effectiveness of case management in the improvement of blood pressure. A critical evaluation of the studies was made and the results of interest were described using the instruments and tools from the Joanna Briggs Institute. Due to the heterogeneity of the included studies, the results of similar measures were not grouped in statistical meta-analysis. A narrative and tabular format was used to synthesize and present them. Results. Six randomized controlled trials were critically evaluated and included in the review. The total sample was 1963 participants. The results showed the outcomes compared at baseline and at the end of follow-up (six or twelve months). Regarding the main outcome, systolic and diastolic blood pressure, there was some reduction in the group followed-up through case management in studies lasting six months; however, the impossibility of comparing the findings poses limitations to answering the questions in this review. Conclusions. Despite the heterogeneity of the studies, the narrative and tabular analysis demonstrated that short-term case management in primary care (six-month studies) helped to reduce blood pressure levels, although the level of evidence for these results is low or very low.